2022
DOI: 10.1039/d1ra04148g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photobiological applications of naphthalimide–benzothiazole conjugates: cytotoxicity and topoisomerase IIα inhibition

Abstract: Conjugates of naphthalimide, benzothiazole, and indole moieties are synthesized that show excellent cytotoxicity against A549 (lung), MCF7 (breast), and HeLa (cervix) cancer cell lines with IC50 values in the range of 0.14–8.59 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
(107 reference statements)
1
5
0
Order By: Relevance
“…The binding of amsacrine to topo IIα is similar to that of etoposide based on the interacting amino acid residues, thus only compounds 58a, 58c, 58f, and 58i showed similar binding, which could be used to infer their anticancer properties. Similar results had been reported for the docking interaction of human topoisomerase IIα (PDB: 1ZXM) with naphthalimide-benzothiazole conjugates and etoposide, which indicated amino acid residues Val57, Gln59, Gln60, Met61, Trp62, Tyr72, Phe77, Pro79, Tyr82, Lys83, Lys306, Gln309, Ile311, Phe313, Ala318, Ser320, Lys321 and Glu379 [29].…”
Section: Discussionsupporting
confidence: 85%
“…The binding of amsacrine to topo IIα is similar to that of etoposide based on the interacting amino acid residues, thus only compounds 58a, 58c, 58f, and 58i showed similar binding, which could be used to infer their anticancer properties. Similar results had been reported for the docking interaction of human topoisomerase IIα (PDB: 1ZXM) with naphthalimide-benzothiazole conjugates and etoposide, which indicated amino acid residues Val57, Gln59, Gln60, Met61, Trp62, Tyr72, Phe77, Pro79, Tyr82, Lys83, Lys306, Gln309, Ile311, Phe313, Ala318, Ser320, Lys321 and Glu379 [29].…”
Section: Discussionsupporting
confidence: 85%
“…Singh et al [88] have reported napthalimide-benzothiazole conjugates as cytotoxic agents. Compounds 37 and 38 (Figure 25)…”
Section: Phosphatidylinositol-3-kinases (Pi3k)/akt Inhibitorsmentioning
confidence: 99%
“…Singh et al [ 88 ] have reported napthalimide‐benzothiazole conjugates as potent cytotoxic agents. Compounds 37 and 38 (Figure 25) were found to be the most potent in the series, exhibiting excellent inhibitory activity with IC 50 values of 0.14 and 0.31 µM against A549 and 3.81 and 3.49 µM against MCF‐7 cancer cell lines, respectively.…”
Section: Benzothiazole Scaffold‐based Enzyme Inhibitorsmentioning
confidence: 99%
“…Benzothiazole-indole-naphthalimide hybrid 37 (IC 50 : 0.38 µM) with low toxic effects (IC 50 : >10 µM) in normal HEK293 cells was comparable to etoposide (IC 50 : 0.33 µM) against MCF-7 cells. [70] The SAR indicated that the naphthalimide moiety and the allyl group at the N-1 position of naphthalimide moiety were vital for the high activity. [70,71] Mechanistically, hybrid 37 might suppress topoisomerase IIα to produce its antiproliferative properties.…”
Section: Indole/isatin-azole Hybridsmentioning
confidence: 99%
“…[70] The SAR indicated that the naphthalimide moiety and the allyl group at the N-1 position of naphthalimide moiety were vital for the high activity. [70,71] Mechanistically, hybrid 37 might suppress topoisomerase IIα to produce its antiproliferative properties. Isatin-1,3,4-thiadiazole hybrid 38 (GI 50 : 0.71-1.98 µM) revealed strong broad-spectrum efficacy against a panel of MCF-7, HS 578 T, BT549, T47D, MDA-MB-231, and MDA-MB-468 BC cell lines, [72] whereas hybrids 39a-c (IC 50 : 9.0 µM) were comparable to doxorubicin (IC 50 : 4.8 µM) against MCF-7 cancer cells.…”
Section: Indole/isatin-azole Hybridsmentioning
confidence: 99%